Enhanced ammonia nitrogen removal using consistent biological regeneration and ammonium exchange of zeolite in modified SBR process - Jung, JY; Chung, YC; Shin, HS; Son, DH (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
The modified zeo-SBR is recommended for a new nitrogen removal process that has a special function of consistent ammonium exchange and bioregeneration of zeolite-floc. Three sets of sequencing batch reactors, control, zeo-SBR, and modified zeo-SBR were tested to assess nitrogen removal efficiency. The control reactor consisted of anoxic-fill, aeration-mixing, settling, and decanting/idle phases, meaning that nitrogen removal efficiency was dependent on the decanting volume in a cycle. The zeo-SBR reactor was operated in the same way as the control reactor, except for daily addition of powdered zeolite in the SBR reactor. The operating order sequences in the zeo-SBR were changed in the modified zeo-SBR. Anoxic-fill phase was followed by aeration-mixing phase in the zeo-SBR, while aeration-mixing phase was followed by anoxic-fill phase in the modified zeo-SBR to carry NH(4)(+)-N over to the next operational cycle and to reduce total nitrogen concentration in the effluent. In the modified zeo-SBR, nitrification and biological regeneration occurred during the initial aeration-mixing phase, while denitrification and ammonium adsorption occurred in the following anoxic-fill phase. The changed operational sequence in the modified zeo-SBR to adapt the ammonium adsorption and biological regeneration of the zeolite-floc could enhance nitrogen removal efficiency. As a result of the continuous operation, the nitrogen removal efficiencies of the control and zeo-SBR were in 68.5-70.9%, based on the 33% of decanting volume for a cycle. The zeo-SBR showed a consistent ammonium exchange and bio-regeneration in the anoxic-fill and aeration-mixing phases, respectively. Meanwhile, the effluent total nitrogen of the modified zeo-SBR showed 50-60 mg N/L through ammonium adsorption of the zeolite-floc when the influent ammonium concentration was 315 mg N/L, indicating the T-N removal efficiency was enhanced over 10% in the same HRT and SRT conditions as those of control and zeo-SBR reactors. The ammonium adsorption capacity was found to be 6-7 mg NH(4)(+)-N/g FSS that is equivalent to 40 mg NH(4)(+)-N/L of ammonium nitrogen removal. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: ION-EXCHANGE; CLINOPTILOLITE